Proportion and associated factors of sexual violence among female night junior school students in Gondar town, Northwest, Ethiopia, 2019 - Woynhareg Kassa Tiruneh; Terefe Derso; Moges Muluneh Boke (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2022)
Introduction: Sexual violence is a series public of health problems and human right issues affecting millions of people each year throughout the world with short and long-term impacts on women and girls' physical, mental, sexual, and reproductive health. Therefore, this study aims to assess the magnitude of sexual violence and associated factors among night school female students in the study area.  Methods: Institution-based cross-sectional study design was conducted among 422 night junior school female students in Gondar town, Northwest, Ethiopia. Participants were selected by using simple random sampling and data were collected by self - administered structured questionnaire. Data entry and analysis was done by EPI info version 7 and SPSS statistical packages version 20 respectively and descriptive statistics were done. Moreover, binary logistic regression analyses were also carried out to identify factors associated with sexual violence. Results: In this study, the mean age (+_SD) study participants was 19.3±3.1years. The the proportion of school life sexual violence in this study was found to be 63.4% with a 95% the confidence interval of (57.9, 67.1). the overall 91 (21.9%) of the participants were faced attempted rape in their school life. Regarding sexual harassment at least one form of sexual harassment was reported among 244 (58.8%) from these 135 (32.5%) unwanted sexual Act/asked to have sex, about 152(36.6%) faced unwelcome touching body parts like breast, and 131 (31.6%) faced unwelcome kissing. School life sexual violence was positively associated with those females who had ever started sexual intercourse (AOR= 0.58, 95%CI, 0.362, 0.924), being rural child-hood residence (AOR=) 1.9, 95%CI 1.2,2.9) and traveling more than 30 minutes from school to home (AOR= 2.2,95%CI, 1.124, 4.452). Conclusion: The proportion of sexual violence in this study area was relatively high and it was significantly associated with being a rural child -hood residence. Therefore, appropriate intervention is needed Especially those students who grew up in a rural areas during the child-hood period.